錄影分析在教育研究的應用 Conducting Video Analysis in Educational Research - 吳心楷 Hsin-Kai Wu; 宋曜廷 Yao-Ting Sun; 簡馨瑩 Hsin-Yin Chien (National Taiwan Normal University, 2010)
近年來，錄影資料在教育研究的應用日漸普遍。本文探討錄影如何成為有效的觀察和研究工具，並且如何應用錄影分析於其他的研究方法中。錄影資料具有忠實紀錄細節、可供重複觀看等特性，然而，錄影資料的轉換及分析過程可能相當複雜，因此，本文圍繞在資料收集、管理和分析三大部分，提供錄影資料登錄、選取和表徵的策略，以實例說明如何將錄影分析應用於量化、質性及混合方法的研究，並簡介七種錄影分析軟體供研究者參考。這些實例顯示，若能善用錄影分析，將之與研究設計有效地結合，可更深入地瞭解所關心的現象。雖然錄影分析有諸多優點，研究者仍應考量其限制並留意研究倫理的議題，本文建議運用同儕審視和多重驗證等策略，以確保分析結果的信度與效度。最後，期待在證據為導向的教育研究中，錄影分析能被有效應用，並進一步擴展教育研究的架構和視野。 Recently, video analysis has been used increasingly more widely in educational research. The purpose of this article is to present how to conduct video analysis in education and discuss its potential benefits, limitations, and ethical issues. The benefits of video data include preserving detailed information of interactions, allowing repeated examination of data, and allowing multidisciplinary analyses; however, the process of video transcription and data reduction could be challenging and complicated. Therefore, this article outlines strategies and procedures for managing, selecting, and representing video data, and provides examples to show how to combine video analysis with quantitative, qualitative, and mixed-methods research. This article also introduces several technological tools for video research. Although there are potential benefits of using video analysis in educational research, researchers should also pay attention to its limitations and related ethical issues, and employ techniques such as member checking and triangulation to ensure the trustworthiness of the analysis. Finally, an effective use of video analysis could support evidence-based research and deepen current understandings of teaching and learning in complex learning environments.